2021
DOI: 10.9778/cmajo.20200247
|View full text |Cite
|
Sign up to set email alerts
|

Health care costs associated with hepatitis C virus infection in First Nations populations in Ontario: a retrospective matched cohort study

Abstract: Background: Colonization and marginalization have affected the risk for and experience of hepatitis C virus (HCV) infection for First Nations people in Canada. In partnership with the Ontario First Nations HIV/AIDS Education Circle, we estimated the publicly borne health care costs associated with HCV infection among Status First Nations people in Ontario. Methods: In this retrospective matched cohort study, we used linked health administrative databases to identify Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
1
6
1
Order By: Relevance
“…This study is part of an ongoing collaboration between the Ontario First Nations HIV/AIDS Education Circle (OFNHAEC), ICES (an independent, nonprofit research institute) and academic researchers, described elsewhere. 4 , 5 , 13 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study is part of an ongoing collaboration between the Ontario First Nations HIV/AIDS Education Circle (OFNHAEC), ICES (an independent, nonprofit research institute) and academic researchers, described elsewhere. 4 , 5 , 13 …”
Section: Methodsmentioning
confidence: 99%
“…We conducted a population-based retrospective cohort study of Status First Nations peoples in Ontario with a confirmed positive test result for HCV antibody or RNA from Jan. 1, 19991, , to Dec. 31, 2018 This study is part of an ongoing collaboration between the Ontario First Nations HIV/AIDS Education Circle (OFNHAEC), ICES (an independent, nonprofit research institute) and academic researchers, described elsewhere. 4,5,13 Guided by Tri-Council Policy Statement chapter 9: Research Involving Indigenous Peoples in Canada, 14 collaboration with OFNHAEC throughout this research ensured the inclusion of First Nations representatives from different Provincial Territorial Organizations and Independent First Nations, patient representatives, Elders, and sexually transmitted and blood-borne infection coordinators and educators across the province. 13 The study was reviewed for compliance with the principles of ownership, control, access and possession (OCAP), 15,16 and approved by the Chiefs of Ontario First Nations Data Governance Committee and Grand Council Treaty #3.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reliable estimates of CHC-attributable healthcare costs are necessary for making appropriate resource allocation decisions among diferent populations and for healthcare planning to meet WHO targets. Several studies have examined CHC costs in Canada [8][9][10]; however, there are no data on the economic burden of CHC among immigrants. Our objective was to estimate CHC-attributable mortality and healthcare costs among immigrants in Ontario, using real-world population-level data.…”
Section: Introductionmentioning
confidence: 99%